2017
DOI: 10.3390/children4060048
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Non-Alcoholic Fatty Liver Disease

Abstract: With the increase in the prevalence of obesity, non-alcoholic fatty liver disease (NAFLD) has become among the leading causes of chronic liver disease in the pediatric age group. Once believed to be a “two-hit process”, it is now clear that the actual pathophysiology of NAFLD is complex and involves multiple pathways. Moreover, NAFLD is not always benign, and patients with non-alcoholic steatohepatitis (NASH) are at increased risk of developing advanced stages of liver disease. It has also been shown that NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 74 publications
0
62
0
4
Order By: Relevance
“…The global prevalence of NAFLD is estimated to be about 24% and represents a massive economic burden on the health care system (3). Notably, NAFLD in the pediatric community has a prevalence of 3%-12% and can affect up to 80% of the obese subpopulation (2,4). NAFLD has a strong genetic component, and familial aggregation studies identified that siblings and parents of children with NAFLD were more likely to manifest fatty liver (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global prevalence of NAFLD is estimated to be about 24% and represents a massive economic burden on the health care system (3). Notably, NAFLD in the pediatric community has a prevalence of 3%-12% and can affect up to 80% of the obese subpopulation (2,4). NAFLD has a strong genetic component, and familial aggregation studies identified that siblings and parents of children with NAFLD were more likely to manifest fatty liver (5).…”
Section: Introductionmentioning
confidence: 99%
“…Parental metabolic syndrome epigenetically reprograms offspring hepatic lipid metabolism in mice Dario F. De Jesus, 1,2,3,4 Kazuki Orime, 1,2,3 Dorota Kaminska, 5 Tomohiko Kimura, 1,2,3 Giorgio Basile, 1,2,3 Chih-Hao Wang, 6 Larissa Haertle, 7,8 Renzo Riemens, 7 Natalie K. Brown, 1,2,3 Jiang Hu, 1,2,3 Ville Männistö, 9 Amélia M. Silva, 10,11 Ercument Dirice, 1,2,3 Yu-Hua Tseng, 6 Thomas Haaf, 7 Jussi Pihlajamäki, 5,12 and Rohit N. Kulkarni 1,2,3 Figure 1. Body weight trajectories and body composition are altered in FL and ML offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric non‐alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases in children and adolescents with a prevalence of 8% in the general population and 26% in children with obesity . Physiologic and psychosocial comorbidities in paediatric NAFLD include atherosclerosis, hypertension, structural cardiac disease, type 2 diabetes, obstructive sleep apnea, anxiety, and impaired quality of life . Over time, paediatric NAFLD is associated with a 13.6‐fold higher risk of death or liver transplantation compared with the general population over 20 years .…”
Section: Introductionmentioning
confidence: 99%
“…Основні групи захворювань печінки, що спостерігаються в дітей, -токсичні, інфекційні, метаболічні, автоімунні, судинні й інфільтративні. Хронічні вірусні гепатити В і С виявляються в пацієнтів незалежно від віку, як і захворювання печінки, викликані експозицією гепатотоксичних препаратів, і пухлини [1,4,9,11,19].…”
unclassified